Analysis of the Impact of Illegal Parking on Consumer Purchase Interest: Case Study of Indomaret Jl. Srijaya Negara, Palembang - Eogenie Lakilaki; Rusdianto; Murlita; Nova Tri Evriani; Muhammad Zaky Ramadhan; Reza Junita (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
The phenomenon of illegal parking in public areas, particularly around shopping centers like Indomaret on Jl. Srijaya Negara, Palembang, has become an urgent issue, disrupting traffic order and affecting consumer purchasing interest. This study explores the impact of illegal parking on consumer purchasing interest at Indomaret Jl. Srijaya Negara, Palembang. The method used in this research is qualitative with a case study design. The study population consists of consumers shopping at Indomaret, with informant selection using a purposive sampling technique. The instrument used is semi-structured interviews, and data analysis is conducted using the Miles & Huberman model. Interview results indicate that illegal parking creates discomfort and concerns about vehicle security, negatively impacting consumer purchasing decisions. In conclusion, illegal parking significantly impacts consumer purchasing interest, and Indomaret management needs to improve parking facilities and security to attract more customers.